Kepastian Nilai Dasar Penghitungan Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) - R. Murjiyanto; Samun Ismaya (Fakultas Hukum Universitas Islam Indonesia, 2015)
The problems in this research are formulated as follow, first, how is the standard value calculated in the transition of BPHTB land rights? Second, how to assure the standard value in the calculation of BPHTB on the transfer of land rights? This research is a normative research supported by empirical data with the approach of legislations. On the basis of this study we concluded that, first, there is uncertain quantification of BPHTB amount to be paid, with the obligation that inhibit the validation process of registration of land rights transfer. Secondly, there should be standard fixed value as the basis for calculating BPHTB by the competent authority, such as the Taxable Value on Property Tax.